2023
DOI: 10.3389/fcvm.2022.1029012
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone vs. metoprolol succinate in HFrEF complicated with persistent atrial fibrillation with rapid ventricular response: A prospective observational study

Abstract: Backgroundβ-blockers have been recommended for patients with heart failure (HF) and atrial fibrillation (AF), but studies have shown that β-blockers do not reduce all-cause mortality or cardiovascular mortality in patients with HF and AF.ObjectiveTo investigate the difference in efficacy between oral amiodarone and metoprolol succinate for patients with HF with reduced ejection fraction (HFrEF) and persistent atrial fibrillation (pAF) with rapid ventricular response (RVR).MethodsPatients with HFrEF complicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…It was previously reported that metoprolol combined with amiodarone for the treatment of patients with acute myocardial infarction and arrhythmia could improve the clinical efficacy and reduce the symptoms of palpitation and chest tightness caused by excessive heart rate [19]. In the present study, the overall rate of effective treatment was found to be significantly higher in the OG than in the CG (p < 0.05), indicating the moracizine and metoprolol combination was superior to metoprolol alone.…”
Section: Discussionsupporting
confidence: 49%
“…It was previously reported that metoprolol combined with amiodarone for the treatment of patients with acute myocardial infarction and arrhythmia could improve the clinical efficacy and reduce the symptoms of palpitation and chest tightness caused by excessive heart rate [19]. In the present study, the overall rate of effective treatment was found to be significantly higher in the OG than in the CG (p < 0.05), indicating the moracizine and metoprolol combination was superior to metoprolol alone.…”
Section: Discussionsupporting
confidence: 49%